Myeloperoxidase, asymmetric dimethyl-arginine and the renin-angiotensin-aldosterone-system in cardiovascular risk patients: cross-sectional findings from the Ludwigshafen Risk and Cardiovascular Health (LURIC) study - Zelzer, Sieglinde; März, Winfried (Clinical biochemistry, 2017)
Objectives: The leukocyte-derived myeloperoxidase (MPO), the nitric oxidase synthase (NOS) inhibitor asymmetrical dimethyl-arginine (ADMA) and the renin-angiotensin-aldosterone-system (RAAS) are associated with cardiovascular diseases (CVD). This study aimed to investigate potential interactions between the RAAS, ADMA and MPO in cardiovascular risk patients. Design and methods. All in all, 1446 patients, who were referred to coronary angiography, were included in this prospective study. MPO, ADMA and circulating serum markers of the RAAS system were measured. Additionally, all-cause and CVD mortality, cardiovascular risk factors, inflammatory and endothelial markers, and medication use were investigated. Results: MPO concentrations were significantly associated with ADMA (P=0.002), renin (P=0.001) and angiotensin II levels (P=0.015), whereas ADMA was in tendency associated with renin (P=0.059) and significantly with angiotensin II (P=0.001). Both, ADMA and MPO were inversely correlated with angiotensinogen, angiotensin I and the angiotensin I/angiotensin II ratio. ADMA and angiotensin II were found stronger independent risk factors for all-cause and CVD mortality compared to MPO. Conclusions: MPO concentrations were significantly associated with higher ADMA levels and an up-regulated circulating RAAS in patients with CVD. Moreover, serum levels of ADMA and angiotensin II were shown to be more predictive for all-cause and CVD mortality compared to MPO.
Available online 18 March 2017
Gesehen am 25.07.2018